Biological Asset: What is The Impact on Agricultural Companies? - Maulida Dwi Kartikasari; Dien Noviany Rahmatika; Sumarno Sumarno (Jurnal Akuntansi dan Pajak, 2021)
This study aims to determine the effect of managerial stock, biological asset intensity and firm size on the disclosure of biological assets in agricultural companies listed on the Indonesian stock exchange in 2016-2019. Population in this study were primary consumer goods sector companies in agricultural companies listed on the Indonesia Stock Exchange. Based on sample selection, there are 52 companies that required The data analysis technique used in this research was the multiple linear regression analysis.. Based on the multiple linear regression analysis, the results show biological asset intensity have a significance below 0.05, namely 0.006. This shows that biological asset intensity have a significant positive effect on biologiocal asset disclosure. However, the firm size and managerial ownership variables have a significance value above 5%. This means that the two variables do not have a significant effect on biological asset disclosure in agricultural companies listed on the Indonesia Stock Exchange in 2016-2019.